Characteristics of biodegradable plastic from cellulose fiber of rice straw (Oryza sativa L.) with glycerol as a plasticizer - Putra, Sahasika Sean; Zainulmuttaqin, Ariki; Viryateja, Gavin; Rahayu, Triastuti (Jurnal Teknika, 2025)
Indonesia faces dual environmental challenges from plastic pollution and agricultural waste accumulation. To address these issues, innovative solutions are needed to transform waste into sustainable materials. This study valorizes rice straw (Oryza sativa L.) cellulose and used cooking oil (UCO) glycerol to develop biodegradable plastics through an accessible method. Cellulose was extracted from rice straw via alkaline (10% NaOH) and bleaching (20% H₂O₂) treatments, while glycerol was recovered from UCO through saponification. Bioplastic films were synthesized by solution casting with varying glycerol volumes (6, 9, 12 mL) and cellulose particle sizes (fine, semi-fine, coarse). Results demonstrated exceptional biodegradability, with ≥ 80% weight loss within 14 days in EM4-supplemented soil burial tests outperforming commercial cassava-based bioplastics (25% degradation). Higher glycerol volumes (12 mL) combined with coarse cellulose maximized water solubility (69.39%) and absorption (14.29%), while lower glycerol (6 mL) with fine cellulose minimized water uptake (5.88%). All formulations exceeded thickness standards (0.438–0.554 mm vs. JIS ≤ 0.25 mm), enhancing rigidity but reducing flexibility. Organoleptic analysis confirmed glycerol content inversely affected transparency and texture smoothness.